(3GdfXGe GdbGfhfj ddGJUGdGJ hGdHK GdEPGYj hGdJdjaRjhfj (B: s (3OQGSI ebGQfI (B/ s - (3gTGe YHOGdZaGQ eMeOs; (3eMehO SejQ GdTQbGhj (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2017)
(3dbO LGAJ Jdc GdOQGSI YbH ebOeJgG GdJj JfGhdJ GdEWGQ GdefgLj GdPj SGQJ Ydjg GdOQGSI(B: (3hGdPj LGA LGeYkG Hjf GdefgL GdebGQf hGdefgL GdJCUjdj hGdefgL GdhUaj hGdefgL GdJMdjdj(B: (3GSJLGHI deG GSJdReJg echfGJ GdHMK hWHjYJgG aj cd echf efgG Ydi MOI(B: (3heG JMJe ef VQhQI QO GdaQhY hGdLRFjGJ Edi CUhdgG GdYGeI aj GdbGfhf (B.. (3LGAJ GdOQGSI eSJgdI QMdJgG GdHMKjI HaUd JegjOj JMJ YfhGf (B"(3GdJYQja HGdGJUGdGJ hGdHK hJbfjGJ hSGFd GdJQGSd(B": (3jJVef KdGKI eHGMK CSGSjI(B: (3JfGhd ChdgG GdJYQja heUWdMGJ GdOQGSI(B: (3eOddkG Ydi CgejI Pdc aj JQSje MOhO GdOQGSI hWHjYI eG JJfGhdg ef eUWdMGJ eJYOOI(B: (3GJSeJ aj CZdHgG HJQcjHI OdGdjI eMOOI hLGA HYVgG aj MGLI hGVMI Edi bOQ ZjQ jSjQ ef GdObI hGdJMOjO(B: (3heMbbkG dPdc YHQ eWdHjf QFjSjjf(B: (3JfGhd GdChd efgeG eaghe GdGJUGdGJ (B- (3Ydi JfhY SjGbGJg (B- (3ceG YQV deaghe GdHK dZI hGUWdGMkG(B: (3heegOkG GdSHjd dJfGhd OdGdI GdWja GdJQOOj (B((3GdeWdH GdKGfj(B) (3HGYJHGQg GdCSGS GdMGce dYed JbfjGJ GdGJUGdGJ hGdHK(B. (3HjfeG LGA GdeHMK GdKGfj eJfGhdkG JbfjGJ GdHK hhSGFd GdJQGSd heQGMd JWhjQgG aj SjGb JGQjNj Ydej(B: (3TGQM dCOb GdJaUjdGJ hGdJbfjGJ GdeSJNOeI(B: (3eHjfkG BdjGJ JWhjQgG YHQ SjGbgG GdRefj GdeeJO(B: (3hSGQOkG dCfhGY gPg GdJbfjGJ aj GdTHcGJ GdSdcjI GdKGHJI(B: (3hGdTHcGJ GddGSdcjI (B((3GdeWdH GdChd(B) (3hhUhdkG (B- (3HJaUjd MQU GdHGMK Ydi Cf jchf LGeYkG dCOb GdJaUjdGJ(B: (3heDcOkG dSfI GdJWhjQ GdJj MOKJ aj gPg GdJbfjGJ (B- (3Edi GdTHcI GdOhdjI ddeYdheGJ (B"(3GdEfJQfJ(B": (3Pdc GdJaUjd GdPj jDcO GdbfGYI HGdOhQ GdeMhQj GdMGce(B: (3GdPj Jbhe Hg gPg GdTHcI GdOhdjI aj SjGbGJfG GdMjGJjI(B: (3ShGA Ydi eSJhi GdCaQGO Ch GdLeGYGJ(B. s
2017. (3CWQhMI (B((3OcJhQGg(B)-s
(3HHdjhLQGajG(B: (3UaMGJ (B675-715.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdGJUGdGJ hGdHKs; (3THcI GdeYdheGJ GdOhdjIs; (3JWhQ GdGJUGdGJ hGdHKs; (3GdeHGOF GdYGdejI dJfXje GdGJUGdGJ hGdHKs; (3GdWHjYI GdbGfhfjI dJcfhdhLjG GdGJUGdGJ hGdHKs; (3GdHfjI GdJTQjYjI dJfXje GdGJUGdGJ hGdHKs; (3GdHK GdGPGYj GdJdaRjhfjs; (3NOeGJ GdgGJa GdeMehds; (3GdefGRYGJ aj bWGY GdGJUGdGJs; (3GdGJUGdGJ hGdHKs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 2017